Tre interventi su rivoluzione e realtà umana - Fagioli, Massimo (Il sogno della farfalla, 2018)
The speech Massimo Fagioli gave at a book exhibition, Libri come, in Rome, in 2014, and those he gave in the same year at an event the weekly magazine Left organized in Rome are being proposed here. In the first case, the psychiatrist of Analisi collettiva commented on the biography of Turkish poet Nazim Hikmet by Joyce Lussu, who translated his works in Italian. In the second, Fagioli intervened at the end of two debates: Future is culture and The Left and secularism. Amongst the recurring topics in the three speeches, there is the one about human beings’ revolutionary experience, the relation with creativity, with secularism, with the female image and the concept of transformation.